Language and infant mortality in a large Canadian province. (October 2016) - Auger, N.; Bilodeau-Bertrand, M.; Costopoulos, A.
Abstract: Objectives: Infant mortality in minority populations of Canada is poorly understood, despite evidence of ethnic inequality in other countries. We studied infant mortality in different linguistic groups of Quebec, and assessed how language and deprivation impacted rates over time. Study design: Population-level study of vital statistics data for 1, 985, 287 live births and 10, 283 infant deaths reported in Quebec from 1989 through 2012. Methods: We computed infant mortality rates for French, English, and foreign languages according to level of material deprivation. Using Kitagawa's method, we evaluated the impact of changes in mortality rates, and population distribution of language groups, on infant mortality in the province. Results: Infant mortality declined from 6.05 to 4.61 per 1000 between 1989–1994 and 2007–2012. Most of the decline was driven by Francophones who contributed 1.39 fewer deaths per 1000 births over time, and Anglophones of wealthy and middle socio-economic status who contributed 0.13 fewer deaths per 1000 births. The foreign language population and poor Anglophones contributed more births over time, including 0.08 and 0.02 more deaths per 1000 births, respectively. Mortality decreased for Francophones and Anglophones in each level of deprivation. Rates were lower for foreign languages, but increased over time, especially for the poor. Conclusions: Infant mortality rates decreased for Francophones and Anglophones in Quebec, but increased for foreign languages. Poor Anglophones and individuals of foreign languages contributed more births over time, and slowed the decrease in infant mortality. Language may be useful for identifying inequality in infant mortality in multicultural nations. Highlights: Infant mortality in minority populations of Canada is poorly understood. We studied infant mortality in French, English, and foreign language groups. Infant mortality decreased over time for all but foreign languages. Poor Anglophones slowed the decrease in infant mortality over time. Research is needed to document the impact of language in other countries.